1990
DOI: 10.1017/s0094837300010186
|View full text |Cite
|
Sign up to set email alerts
|

Gross spinal anatomy and limb use in living and fossil reptiles

Abstract: The spinal quotient (S.Q.) is an osteologically defined estimate of the enlargement of the spinal cord at limb levels over that at interlimb levels. It is an efficient predictor of limb use in living reptiles and birds and may be used to predict limb function in fossil vertebrates. Among living reptiles, this ratio of limb to interlimb innervation is greatest in arboreal genera, followed by terrestrial sprawlers, aquatic forms, and undulatory forms. Birds show a wide range of brachial S.Q. values that are roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Giffin () introduced hypotheses formulated on these data to the field of palaeobiology; she described how correlations between the relative size of the spinal cord and increased innervation were linked to locomotory function and lifestyle in living animals, an idea then applied to a selection of fossil reptiles and mammals following examination of data on inferred nerve pattern and size. She found a close relationship between the size of the neural canal and size of the spinal cord (Giffin , ), though the relative size of the spinal cord compared to the neural canal does vary (Giffin ). She found that in Alligator mississippiensis , the cross‐sectional area of the spinal cord is relatively constant throughout the vertebral column, occupying a maximum of 47% (in the brachial and lumbosacral maxima), and a minimum interlimb segment fill of 38%.…”
Section: Institutional Abbreviationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Giffin () introduced hypotheses formulated on these data to the field of palaeobiology; she described how correlations between the relative size of the spinal cord and increased innervation were linked to locomotory function and lifestyle in living animals, an idea then applied to a selection of fossil reptiles and mammals following examination of data on inferred nerve pattern and size. She found a close relationship between the size of the neural canal and size of the spinal cord (Giffin , ), though the relative size of the spinal cord compared to the neural canal does vary (Giffin ). She found that in Alligator mississippiensis , the cross‐sectional area of the spinal cord is relatively constant throughout the vertebral column, occupying a maximum of 47% (in the brachial and lumbosacral maxima), and a minimum interlimb segment fill of 38%.…”
Section: Institutional Abbreviationsmentioning
confidence: 99%
“…While the pigeon ( Columba livia ) generally has a relatively larger spinal cord (73% maximum vs 53% minimum fill of interlimb segments) the overall pattern is the same. The lumbosacral regions of both the pigeon and the ostrich have spinal cord fills that are lower than the brachial and interlimb segments as well as in Alligator (29% and 32%, respectively; Giffin ). This is due to the presence of the glycogen body of birds, a structure not found in any other living vertebrates, or in the brachial region of birds.…”
Section: Institutional Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting feature of the lumbosacral intumescence of the spinal cord in birds is its dorsal split ("cleft" in Jelgersma 1951, "groove" in Necker 2005 leading to the formation of the so−called dorsal rhomboid (or lumbosacral) spinal fossa (or sinus). The fossa houses an enigmatic ovoid glial structure called the glyco− gen body (Jelgersma 1951;Breazile and Kuenzel 1993;Butler and Hodos 2005;Kai− ser 2007; see also Giffin 1990). The position of the lumbosacral intumescence and glycogen body can be easily located, for the corresponding part of the synsacral canal is enlarged (Necker 2006).…”
Section: Synsacral Canal and Its Anticipated Contentsmentioning
confidence: 99%